(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Science and technology is seen as the key factor supporting the performance of regional innovation systems. Furthermore, the innovation intensity in the region could be often crucial for regional economic development. Our research aims to examine the potential link between the economic development of the region and the intensity of science and technology activities proxied by the share of employees in science and technology. The analysis is based on panel data for NUTS2 regions of EU member states in the period 2003-2014. We conducted correlation analysis, panel Granger causality tests and regression analysis. Our results suggest the existence of a significant positive correlation between GDP per capita and the share of employees in science and technology. Moreover, the regions with higher intensity of science and technology activities are mostly characterized by relatively low unemployment rates and a higher proportion of residents with a university education. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.